More for less: Analysis of the performance of avian acute oral guideline OECD 223 from empirical data. (11th May 2017) - Edwards, Peter J; Leopold, Annegaaike; Beavers, Joann B; Springer, Timothy A; Chapman, Peter; Maynard, Samuel K; Hubbard, Patrick
ABSTRACT: Since the publication of the Organisation for Economic Co‐operation and Development (OECD) avian acute oral guideline, OECD 223, empirical data have become available to compare the performance of OECD 223 with statistical simulations used to validate this guideline and with empirical data for US Environmental Protection Agency Office of Chemical Safety and Pollution Prevention (USEPA OCSPP) guideline OCSPP 850.2100. Empirical studies comprised 244 for Northern bobwhite, of which 73 were dose–response tests and 171 were limit tests. Of the dose–response tests, 26 were conducted to OECD 223 (using 3–4 stages) and 33 to OCSPP 850.2100 (using the single 50‐bird design). Data were collected from 5 avian testing laboratories from studies performed between 2006 and 2013. The success with which the LD50 and slope could be determined was 100% and 96% for OECD 223 (mean 26 birds per test) and 100% and 51% for OCSPP 850.2100 (mean 50 birds per test). This was consistent with the statistical simulations. Control mortality across all species and designs amounted to 0.26% ( n = 2655) with only single mortalities occurring in any 1 study and <1% for any 1 species. The simulations used to validate the OECD 223 design showed that control mortality up to 1% will have no observable impact on the performance. The distribution of time to death for Northern bobwhite, zebra finch, and canary were obtained from 90, 29, and 17 studies, and mortalities appeared within 3 d for 71%, 95%, and 91% of birds tested, respectively. Integr Environ Assess Manag 2017;13:906–914. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: Empirical data for OECD 223 are consistent with OECD Validation Report 131. The LD50 and slope delivered 100% and 96% of time with 24 birds in test. No impact of low control and delayed mortality on estimates of LD50 and slope. Fifty percent fewer birds required to estimate acute toxicity with OECD 223 than with OCSPP 850.2100.